Towards of Smart Cities Based on the Sustainability of Digital Services - Faaeq, Munadil K.; Mat, Nik Kamariah Nik; Faieq, Alaa Khaleel; Rasheed, Mohammad M.; Faieq, Qusay H. Al- (International Journal of Engineering and Technology, 2018)
Nowadays, the Digital Services (DS) has become an important component of Information Communication Technology (ICT) provided by governments to sustain and facilitate all the transactions. Simuntinuslly, digital services has gained popularity in developed and developing countries alike. Due to the importance of the sustainability of Information System (IS),Â this paper identifies the emergence of a clear gape to measure the sustainability of DS development for transforming to smart cites. The purpose of this paper is to observe the connections between Digital Services as a tool for economic development to approach the smart city and sustainability as the goal. Variables like infrastructure, social factors, security, users behavior and the more are to be determined majorly effecting the sustainability of DS as a technological and psychological packages. With the perspectives of the Expectation-Confirmation Theory (ECT) and Unified Theory of Acceptance and Use of Technology (UTAUT2). To examine the sustainability model, the data for this study were collected from 350 employees in public universities. This study employed the PLS 3 to the measurement model. Based on the findings, it can be confirmed that this freamwork is reliable to measure the sustainability of DS for transforming to smart cites. In addition, the results supported that these are successful key measurements of transforming to smart cities by countinue usage of DS in general and electronic govemrnt (eG) in spicific.